2018
DOI: 10.1111/papt.12168
|View full text |Cite
|
Sign up to set email alerts
|

Is the widely used two‐factor structure of the Ruminative Responses Scale invariant across different samples of women?

Abstract: Objectives Although the Ruminative Responses Scale is one of the most widely used measures of rumination, its two‐factor structure remains controversial. Taking this into account, we aimed to test the RRS‐10 two‐factor invariance (Brazilian version) between different samples of women and to study its internal consistency and convergent validity. Methods A sample of 321 women (general population, n = 106; college students, n = 115; and medical population of patients with overweight and obesity, n = 100) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
3
7
0
Order By: Relevance
“…Prior research studies that has examined gender differences in rumination have included studies that are based on samples of undergraduates (e.g., Butler & Nolen-Hoeksema, 1994; Cheung, Gilbert, & Irons, 2004), and a meta-analysis of gender differences in rumination and adults found no evidence for heterogeneity of effect sizes (Johnson & Whisman, 2013), suggesting that the size of the gender difference in rumination did not differ significantly across studies, including across studies that did versus those that did not involve undergraduates. Furthermore, one study found evidence for metric invariance of a Brazilian version of the 10-item RRS across three samples of women (i.e., a college student sample, a general population sample, and a medical population sample of women in treatment for weight loss; Lucena-Santos, Pinto-Gouveia, Carvalho, & Oliveira, 2018), which supports our decision to test for measurement invariance of the 10-item RRS in college students. However, the possibility remains that the results obtained in this study may not generalize to young adults who are not in college, or who have clinically elevated levels of depression, and research on measurement invariance of the RRS in these samples is warranted.…”
Section: Discussionsupporting
confidence: 67%
“…Prior research studies that has examined gender differences in rumination have included studies that are based on samples of undergraduates (e.g., Butler & Nolen-Hoeksema, 1994; Cheung, Gilbert, & Irons, 2004), and a meta-analysis of gender differences in rumination and adults found no evidence for heterogeneity of effect sizes (Johnson & Whisman, 2013), suggesting that the size of the gender difference in rumination did not differ significantly across studies, including across studies that did versus those that did not involve undergraduates. Furthermore, one study found evidence for metric invariance of a Brazilian version of the 10-item RRS across three samples of women (i.e., a college student sample, a general population sample, and a medical population sample of women in treatment for weight loss; Lucena-Santos, Pinto-Gouveia, Carvalho, & Oliveira, 2018), which supports our decision to test for measurement invariance of the 10-item RRS in college students. However, the possibility remains that the results obtained in this study may not generalize to young adults who are not in college, or who have clinically elevated levels of depression, and research on measurement invariance of the RRS in these samples is warranted.…”
Section: Discussionsupporting
confidence: 67%
“…For the reliability analysis of the RRS-10, all Cronbach's α coefficients, in both the undergraduate sample and clinical sample, reached acceptable standards (α > 0.70). These results were consistent with previous studies, which reported the internal reliability from 0.74 to 0.92 (8,(13)(14)(15)(16)(17)(18)(19). All the mean inter-item coefficients were between 0.10 and 0.40 both in the undergraduate sample and clinical sample and the high test-retest values also indicated good reliability of the RRS-10.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Arana et al explored the fact that the two-factor structure only retained eight of the original items (excluding item 2 and item 9) (25). A confirmatory study found that the original two-factor model was not confirmed among a community sample (17). A number of studies in recent years have confirmed that different types of rumination have different effects on depression: brooding is a risk factor which may prolong or exacerbate depression, while reflection is a protective factor which does not prolong depression (11,26).…”
Section: Introductionmentioning
confidence: 99%
“…The previous researched have analysis the measurement invariance of two factor-model (GFI = 0.91, CFI = 0.89, TLI = 0.85, RMSEA = 0.08) (50). Some researches also discussed the factorial invariance across different samples, such as different populations and different countries (Lucena-Santos et al, 2018;Arana & Rice, 2017). According to the previous research, the result of the two-factor model suggested that the 10-item version of the RRS provided an assessment of psychometrically equivalent across gender (Whisman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies, Butler and Nolen-Hoeksema (Butler & Nolen-Hoeksema, 1994) used a two-factor version with 10 items. So more researches discussed the reliability and validity of the two factors of RRS (Hasegawa, 2013;Lei et al, 2017;Lucena-Santos et al, 2018), but less researches focused on the reliability and validity of the three factors. The RRS has emerged as the most frequently used self-report measure of depressive rumination in both researches and clinical practice for its wide target population and stable reliability and validity in Japanese, Dutch and Korean (Topper et al, 2014;Shin, Cho, & Kim, 2015).…”
Section: Introductionmentioning
confidence: 99%